c - MacDonald, Amy (South Melbourne, Victoria : Oxford University Press, 2018)
Mathematics in Early Childhood Education provides students with a range of options for teaching mathematics to young children, by showing how to adapt education practice to suit early childhood contexts, including home, playgroup, childcare, preschool, and school. The text is informed by, and presents, current Australasian and international research relevant to early childhood mathematics education to help pre-service teachers increase confidence and build up a comprehensive professional identity as a mathematics educator.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Elementary); Mathematics -- Study and teaching (Early childhood)